2017
DOI: 10.1002/bab.1544
|View full text |Cite
|
Sign up to set email alerts
|

A camelid nanobody against EGFR was easily obtained through refolding of inclusion body expressed in Escherichia coli

Abstract: Using anti-EGFR (epidermal growth factor receptor) nanobody is a good choice for diagnoses and therapeutics for high EGFR expression diseases. In the present study, the percentage composition of anti-EGFR nanobody attained 25% of the total cell protein expressed in Escherichia coli BL21 (DE3). However, almost all nanobodies were expressed as inclusion bodies. To acquire active nanobodies, a series of dilution refolding procedures were optimized after inclusion bodies were dissolved into 6 M urea and purified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition to the advantages already conferred upon them due to their smaller size, Nbs possess a whole host of favorable biochemical characteristics. Firstly, Nbs exhibit remarkable stability when exposed to high temperatures for prolonged periods which is in part due to their extended CDR3 and their ability to refold after denaturation [ 4 , 38 , 39 , 40 , 41 ]. It has also been shown that thermal stability can be further increased by means of selecting Nbs with an additional second disulfide bond, extending the length of the CDR3, and mutations of specific amino acid residues at the N-terminal [ 42 , 43 ].…”
Section: Desirable Properties Of Nanobodies Over Conventional Monoclo...mentioning
confidence: 99%
“…In addition to the advantages already conferred upon them due to their smaller size, Nbs possess a whole host of favorable biochemical characteristics. Firstly, Nbs exhibit remarkable stability when exposed to high temperatures for prolonged periods which is in part due to their extended CDR3 and their ability to refold after denaturation [ 4 , 38 , 39 , 40 , 41 ]. It has also been shown that thermal stability can be further increased by means of selecting Nbs with an additional second disulfide bond, extending the length of the CDR3, and mutations of specific amino acid residues at the N-terminal [ 42 , 43 ].…”
Section: Desirable Properties Of Nanobodies Over Conventional Monoclo...mentioning
confidence: 99%
“…High local concentrations of the nascent heterologous protein together with an insufficient amount of folding-promoting chaperons may lead to partially folded or misfolded protein intermediates that give rise to the formation, in both the cytoplasm and periplasm, of insoluble protein aggregates known as inclusion bodies, IBs [77]. Usually, these intermediates expose on their surface hydrophobic patches that interact with similar regions and together with the formation of uncorrected disulfide bonds can lead to protein aggregation and precipitation Protein recovery strategies from inclusion bodies via solubilization and refolding processes are laborious, time-consuming and expensive, although various refolding procedures have been developed for therapeutic proteins and applied for antibody fragments [78][79][80]. An introduction to the IB refolding procedure [81] is outside the scope of this review.…”
Section: Inclusion Bodiesmentioning
confidence: 99%